Nutrient Requipement of Mango- Ginger (Curcuma amada Roxb.) - Mridula KR (Department of Horticulture, College of Agriculture, 1997)
A field experiment was conducted at the College of Agriculture, Vellayani, during the period June-December 1995, to study the effects of different doses of nitrogen, phosphorus and potassium on the growth, yield and quality of mango-ginger. The treatments consisted of factorial combinations of 3 levels each of nitrogen (15, 30 and 45 kg N ha-1), phosphorus (15, 30 and 45 kg P2O5 ha-1) and potassium (30, 60 and 90 kg K2O ha-l) with absolute control. The experiment was laid out as 33+1 Factorial Randomised Block Design with three replications. Nitrogen (30 kg ha-1) recorded maximum values for most of the characters namely plant height, leaf area index, dry matter production, crop growth rate, bulking rate, top yield, fresh rhizome yield, recovery of dry rhizome, volatile oil. Application of highest dose namely, 45 kg N ha-l resulted in highest number of tillers, number of leaves, utilization index, harvest index, non-volatile ether extract, fibre content and chlorophyll content. Phosphorus (30 kg ha-1) registered higher values for plant height, number of leaves, leaf area index, bulking rate, rhizome spread, fresh rhizome yield and recovery of dry rhizome. Application of 45 kg P205 ha-1 produced maximum sprouting, number